The role of soluble common gamma chain in autoimmune disease - Lee, Byunghyuk; Hong, Changwan (Anatomy & cell biology, 2015)
The common gamma chain (γc) is the central signaling unit for a number of cytokine receptors collectively known as the γc cytokine receptor family. γc is critical for ligand binding and signaling by γc cytokines. γc cytokine signaling had been thought to be mainly regulated by cytokine-specific receptor α chain expression levels with little or no effect by γc surface levels because γc expression was presumed to remain unchanged during T-cell activation and development. The extent of γc cytokine responses is thought to be regulated by cytokine specific receptor subunits and not by the γc receptor. In contrast to this prevailing view, we have recently reported that γc itself actively regulates γc cytokine responses. Interestingly, γc exerted its regulatory effects not only as a conventional membrane receptor protein but also as a secreted protein whose expression was upregulated upon T-cell stimulation. Here we will review how a soluble form of γc, which is generated by alternative splicing, regulates γc cytokine signaling and plays a role in controlling immune activation related to autoimmune disease.